El estudio de la asignatura de Derecho Canónico en los planes de estudio de Derecho, especial relevancia en las universidades de la Comunidad de Madrid - Talavero Cabrera, Víctor (Cauriensia, 2023)
Canon Law is a body of law that regulates the organization and functioning of the Catholic Church and, for many years, has been studied as a compulsory subject in the Faculties of Social and Legal Sciences. The subject study has been relegated, and in many universities is either not taught or, if it is taught, it is optional. The aim of this research work is to carry out a study on the representation and inclusion of this subject in the new Autonomous Community of Madrid universities syllabus. The main objective is to address the importance of Canon Law in jurists training and, also, analyze the possible reasons that could explain this trend in curricula.